Physiological demands of road sprinting in professional and U23 cycling. A pilot study - Menaspà, P.; Quod, M.; Martin, D. T.; Victor, J.; Abbiss, C. R. (Journal of Science and Cycling, 2013)
This pilot study described and compared the power output (absolute, relative to body weight and relative to frontal area) recorded during successful road sprints in professional and under 23 men`s cycling races. The study also described the exercise intensity and requirements of sprinters throughout final 10 min of the race. Nine successful (top 3) sprints performed by a professional (PRO: 23 y old, 1.76 m, 71.8 kg) and an under 23 (U23: 18 y old, 1.67 m, 63.2 kg) cyclist sprinter were analysed in this study. No statistical differences were found in absolute peak and average sprint power (PRO: 1370±51 W and 1120±33 W; U23: 1318±60 W and 1112±68 W). The average power output relative to body weight and to projected frontal area (Ap) was lower in PRO than U23 (15.6±0.4 and 17.4±1.1 W/kg; and 2533±76 and 2740±169 W/Ap, respectively) (P=0.016). The intensity of the last 10 min prior to the sprint was significantly higher in PRO than U23 (4.6±0.3 and 3.7±0.2 W/kg, respectively) (P<0.05). Races duration, total elevation gain and average power were similar between PRO and U23. In conclusion, the physiological demands leading into road sprinting (intensity of the last 10 min) were found to be higher in PRO compared to U23 races; however, a similar sprint power output (>2500 W·Ap-1 or >15.5 W/kg for approximately 14 s, with a peak power output >3100 W/Ap or >19 W/kg) indicates that sprint characteristics may be somewhat similar between PRO or U23 races. Further research is warranted in order to better understand physiological and tactical aspects important to road sprint cycling.